PENGARUH FAKTOR-FAKTOR MOTIVASI TERHADAP KINERJA GURU TIDAK TETAP DI KABUPATEN SUMBAWA - Wahyu Haryadi; Eka Hidayatunnisa; Sri Rahayu (Fakultas Ekonomi dan Manajemen, 2022)
This study aims to examine how much influence motivational factors have on the work of temporary teachers at State Vocational Schools in Sumbawa Regency. This research is a causal associative research using a quantitative approach. The motivational factors that will be examined consist of education, salary, gender, culture, social status and responsibility as independent variables, while teacher performance is not fixed in Sumbawa Regency as the dependent variable. The type of data used in this study is quantitative data obtained from primary sources, namely all non-permanent teachers at various State Vocational Schools in Sumbawa Regency, totaling 30 respondents. researchers used questionnaires as primary data collection instruments and studied using techniques that included simple linear regression analysis, individual parameter hypothesis testing (t test), simultaneous parameter hypothesis testing (F test), and determinant coefficient test (R2). The results of this study indicate that education, salary, gender, culture, social status and responsibility have a positive and significant effect on the performance of temporary teachers in Sumbawa District, either partially or simultaneously. The degree of influence of education, salary, gender, culture, social status and responsibility on the performance of non-permanent teachers in Sumbawa Regency is 82.5%, while the remaining 17.5% is influenced by other variables outside this research model.